Learning styles and strategies for management students - Carvalho, Luisa Cagica 1970-; Noronha, Adriana Backx 1969-; Souza, Crisomar Lobo de 1959- (IGI Global, 2020)
"This book explores emerging and innovative aspects of educational practices through concepts and principles of learning styles and strategies"--Provided by publisher"--
Description based on title screen (IGI Global, viewed 04/15/2020)
Keywords: Education, Higher / Aims and objectives; Educational change; Management / Study and teaching (Higher)